Evaluation of Fracture Resistance of Asphalt Mixtures Using the Single-Edge Notched Beams - Biao Ding; Xiaolong Zou; Zixin Peng; Xiang Liu (Advances in Materials Science and Engineering)
To determine and compare the fracture properties of different asphalt mixtures, single-edge notched beam (SENB) tests using three types of asphalt mixtures were applied in this study under the conditions of different notched depths and different temperatures. The effects of notched depths and temperatures on the fracture toughness and fracture energy were analyzed. The results indicate that the notch depth has no significant effects on the fracture toughness and the fracture energy, but the gradation has relatively obvious effects on the fracture energy, which the larger contents of course aggregate leads to increase the discreteness of the fracture energy of the specimen. The temperature has significant effects on the ultimate loads, fracture energy, and fracture toughness. The ultimate loads of the SENBs reach the peak value at 0°C, which could be resulted in that viscoelastic properties of asphalt mixture depend with temperatures. The fracture toughness at −20°C of continuously graded asphalt mixtures are higher than those of gap-graded asphalt mixtures. On the contrary, the fracture toughness of gap-graded asphalt mixtures is higher at temperatures from −10°C to 20°C. The fracture energy increases with temperatures, and the fracture energy of SMA-13 is significantly larger than those of AC-13 and AC-16.